The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1516-35982010000600021
|View full text |Cite
|
Sign up to set email alerts
|

Performance and carcass characteristics of Santa Inês pure lambs and crosses with Dorper e Texel at different management systems

Abstract: -It was evaluated the performance and the carcass characteristics of 36 non-castrated male lambs, Santa Inês purebreed and crossbreeds from Dorper × Santa Inês and Texel × Santa Inês, managed in three different systems (intensive, semi-intensive and extensive), slaughtered at 38.41 ± 1.24 kg. It was observed the highest weight gain for lambs reared in intensive system, which also showed the greatest carcass yield. The management systems did not influence carcass measures of animals in intensive system much bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 11 publications
5
6
2
6
Order By: Relevance
“…Variation in pregrazing pasture heights was not sufficient to cause large enough variations in nutritional forage to modify the HCY. The hot carcass yield obtained was close to that observed by Garcia et al (2010) for pure and crossed Santa Ines sheep only in Aruana grass pasture (41.9%), while the group that received supplementation had higher hot carcass yield. The authors attribute this result to the diet having a greater allowance of nutrients, and thus greater development of the main parts that compose the carcass (muscle, bone and fat) compared to other parts of the body.…”
Section: Discussionsupporting
confidence: 78%
“…Variation in pregrazing pasture heights was not sufficient to cause large enough variations in nutritional forage to modify the HCY. The hot carcass yield obtained was close to that observed by Garcia et al (2010) for pure and crossed Santa Ines sheep only in Aruana grass pasture (41.9%), while the group that received supplementation had higher hot carcass yield. The authors attribute this result to the diet having a greater allowance of nutrients, and thus greater development of the main parts that compose the carcass (muscle, bone and fat) compared to other parts of the body.…”
Section: Discussionsupporting
confidence: 78%
“…Although the latter have low carcass conformation, Souza et al (2016) found no difference in body score of Santa Inês, ½ Dorper × Santa Inês and ¾ Dorper × Santa Inês lambs. Garcia et al (2010) reported similarity between quantitative variables of Santa Inês, Texel × Santa Inês, and Dorper × Santa Inês lambs, corroborating the results obtained in the present study, which found no difference among the groups analyzed regarding CCW, tissue composition, or fat cover.…”
Section: Discussionsupporting
confidence: 92%
“…The meat: bone ratio was in the range of 1.89:1(T 3 ), 1.92:1(T 2 ) and 2.22:1 (T 1 ) indicated that significantly (p<0.05) higher percentage of meat weight obtained in intensive system. Higher fat % in intensive farming system was observed by Garcia et al, (2010). Significantly higher fat depots were found in animals fed concentrate feed in intensive group (Ripoll et al, 2014).…”
Section: Body Condition Scores Of Deccani Lambs At Different Growth Smentioning
confidence: 85%